The integration of social and health sectors in Scotland: An analysis from the prism of different public policy models - Matos, R. C. de.; Nascimento, G. do.; Fernandes, A. C.; Matos, C. (Journal of Market Access & Health Policy, 2025)
The integration of health and social care has been a key focus in Scotland, driven by demographic changes, rising healthcare costs, and the need for more efficient service delivery. The Public Bodies (Joint Working) (Scotland) Act 2014 sought to formalise this integration by restructuring governance and service provision to improve coordination between health and social care sectors. Despite these efforts, challenges remain in fully achieving the intended outcomes of the integration. This study analysed Scotland’s integrated health and social care through the theoretical frameworks of public choice, institutionalism, and functionalism. The objective was to examine policy drivers, structural mechanisms, and governance implications, providing insights into the broader impact of integrated care reforms. A qualitative research approach was employed, synthesising data from peer-reviewed literature, government publications, and policy documents. The findings on integration were systematically examined through the lens of each public policy model, allowing for a nuanced analysis of how Scotland’s approach to integration aligns with and diverges from these frameworks. A literature search was performed on PUBMED, Google Scholar, and Scottish government portals. While integration improved coordination and service delivery in some areas, limitations in funding allocation, workforce distribution, and governance autonomy limited its overall success. Scotland’s integrated care model demonstrates potential benefits in reducing service fragmentation and improving patient-centred care; however, persistent challenges such as funding constraints, workforce shortages, and governance conflicts indicate that integration alone is not sufficient to resolve systemic healthcare inefficiencies. This study provides a perspective on Scotland’s health and social care integration, offering valuable lessons for other European countries facing similar demographic and healthcare challenges.